Emona and its pre-Roman population: epigraphic evidence - Šašel Kos, Marjeta (Arheološki vestnik, 2017)
Not much is known about the pre-Roman inhabitants of Emona and their descendants, therefore it is all the more important to collect all available evidence. Epigraphic documents from the Ig area are abundant, containing a large selection of indigenous personal names, which, in contrast, are rather scarce at colonia Iulia Emona, but not as scarce as has been assumed. The tombstones with indigenous names in actuality represent 10.7% of all Emonian grave monuments with identifiable names. At least eight monuments with epichoric anthroponymy can be regarded as having been undoubtedly discovered at Ljubljana. The Emona–Ig areas were closely interdependent in the pre-Roman period and it was only with the foundation of a Roman colony at Emona that the earlier connections and identity of the pre-Roman inhabitants of Emona were forcibly disrupted, relegating the majority of them to a marginal existence. However, there were some who managed to integrate themselves into the Roman society, earning enough money to erect a funeral monument for themselves and their families. This was the case of Buio and his wife Lasciontia, as well as of Enno and his wife Cetetiu. There were native families who were given citizenship, transforming their personal names into a gentilicium, as, for example, the Vibunnii. These names and social connections of their bearers shed a most interesting light on life in Emona before it became a Roman city, as well as on various means of integration, when the former inhabitants had to live side by side with the newcomers.